Metaphor and Ideology - Descamp, Mary Therese (BRILL, 2007)
This cognitive linguistic analysis of Liber Antiquitatum Biblicarum demonstrates how women are used to articulate Pseudo-Philo's theology and ideology; how 'mother' is redefined to support female authority to interpret and instruct; and how textual and character authority is constructed conceptually.
Description based on publisher supplied metadata and other sources
Keywords: Philo; Antiquitates biblicae; Metapher; Ideologie; Erzähltheorie; Rhetorik